Strength Evolution of Ice Plume Deposit Analogs of Enceladus and Europa. Issue 15 (7th August 2020) - Choukroun, M.; Molaro, J. L.; Hodyss, R.; Marteau, E.; Backes, P.; Carey, E. M.; Dhaouadi, W.; Moreland, S.; Schulson, E. M.
Abstract: Enceladus and possibly Europa spew materials from their internal ocean into their exosphere, some of which are deposited back onto the surface of those Ocean Worlds. This setting provides a unique opportunity to seek traces of past or extant life in ice plume deposits on their surfaces. However, the design of lander missions and surface sampling techniques and the choice of sampling locations rely heavily on strength expectations. Here we present an experimental investigation of the evolution in strength of ice plume deposit analogs at several temperatures, as well as a model that predicts first‐order estimates of the strength of evolved ice plume deposits under geologic timescales relevant to Enceladus and Europa. These results suggest that plume deposits remain weak and poorly consolidated on Enceladus, while they may develop substantial strength (comparable to solid ice) within <100 Myr on Europa. Plain Language Summary: Enceladus and Europa are Ocean Worlds; they harbor an internal ocean beneath their ice shells. There is proof that a plume emits ocean materials out of Enceladus, similar to geysers on Earth, and some evidence for similar activity on Europa. Based on the composition of the plumes and the surface, both Enceladus and Europa are the leading outer solar system candidates for possibly harboring life. Areas where fresh plume materials are deposited would be the best location to search for traces of life on the surface. A major challenge in preparing mission concepts to explore these locations arises from the need to collect samples of the surface ice, while little is known at present about the mechanical properties of the surface. In this study, we prepared icy plume deposit analogs and let them evolve in the laboratory over extended periods of time to investigate the evolution of their strength. We find that plume deposits are likely to remain loose and exhibit a low strength over geologic timescales under Enceladus's conditions, suggesting that they would be relatively easy to sample. Conversely, under Europa's surface conditions, such plume deposits appear likely to develop a substantial strength. Key Points: The cone penetration resistance of fine‐grained porous ice held under isothermal conditions increases linearly over time The temperature dependence of the strengthening rate yields an activation energy similar to self‐diffusion at the surface of ice grains Plume deposits would remain weak on Enceladus, while they may develop substantial strength within a few million years on Europa